SCIENTIFIC AND PRACTICAL PROPOSALS ON THE CHOICE AND APPLICATION OF STRATEGIC CONTROLLING INSTRUMENTS AT THE ENTERPRISE IN THE MODERN CONDITIONS - Lyudmyla Malyarets; Olena Iastremska (Сучасний стан наукових досліджень та технологій в промисловості)
The object of the research is the processes of selection and application of strategic control instruments in the enterprise in modern conditions. The subject of the study is the scientific and practical principles that consist of a theoretical approach to the definition of the content of strategic control in the system of strategic management of the activity of the industrial enterprise, the informational and analytical provision of the method of strategic deviations as an adequate and effective modern instrument of strategic controlling. The aim is to formulate recommendations on the choice and application of strategic controlling instruments at the enterprise in modern conditions. Tasks: systematization of strategic controlling instruments at the enterprise in the modern conditions, taking into account the relevant requirements;  development of the technology of the choice of instruments of strategic controlling of the activity of the industrial enterprise; formation of a system of controlled indicators for strategic controlling in industrial enterprises; development of analytical instruments for implementing strategic controlling. Methods. The theoretical analysis of the work of specialists on controlling allowed to form the advantages and disadvantages of each of the strategic control instruments. The analysis and synthesis of the content of strategic controlling allowed to develop a technology of choice of instruments for carrying out strategic controlling activity at an industrial enterprise. To implement the method of strategic deviations it is recommended to solve an optimization problem. The following results were obtained: the proposed system of controllable indicators of the industrial enterprise activity in four types of activities: financial, production, marketing, personnel. In order to determine the optimal values of indicators that can be achieved, taking into account the real possibilities of an enterprise, it is recommended to solve an optimization problem, the solution of which provides optimal values of the indicators. As a target function in the optimization problem, the dependence of the integral indicator (I) of the enterprise's activity development on its most influential controlled indicators, determined on the basis of ranking by means of multivariate statistical factor analysis and multiple regression analysis, should be considered. The system of constraints in the optimization task should be made taking into account real intervals of changes in the values of the indicators of activity of each individual enterprise, in particular taking into account the minimum and maximum values of the indicators that the enterprise had during a certain period. Conclusions: The improvement of the modern effective instrument of strategic controlling is a procedure for determining the desired values of controlled indicators of the enterprise, which forms the information basis for the process of forming a functional strategy and ensures the reality of their implementation.